Model Transportasi Multimoda Distribusi Garam: Studi Kasus Pulau Madura - Nur, Hasan Iqbal; Achmadi, Tri; Fahmi, Ali (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2017)
Indonesia is one of the salt importing countries, although most of its territory is the sea. The current pattern of salt distribution needs to be reviewed, since in reality the production of salt farmers is abundant, but not yet fully absorbed by the salt processing companies. In addition there is a considerable price disparity in salt price between producer and consumer areas. Therefore, in this study we analyze two conditions, which include the salt ditribution pattern in upstream and downstream. Where the upstream area is from the salt producer areas in Madura, there are Bangkalan, Sampang, Pamekasan, and Sumenep to the Salt Processing Factory (PPG). While the downstream area is from the Salt Processing Factory (PPG) to the consumer areas in Jakarta and Denpasar. By using the optimum salt distribution and transportation patterns by the optimization model, there is a decrease in shipping cost per year for each PPG when compared to the current conditions. From PPG Gresik, the cost can be reduced by 26.57% or 7.9 Billion annually, from PPG Surabaya can be reduced by 24.33% or by 7.8 Billion per year and from PPG Sidoarjo can be reduced 17.20% or by 10, 2 billion per year. Thus the price of salt in Jakarta can be decreased by 12% and in Denpasar can be decreased by 8%.